18F-Fluorocholine Uptake and Positron Emission Tomography Imaging in Rat Peritoneal Endometriosis. (January 2018) - Silveira, Marina B.; Rodrigues, Daisy M.; Araújo, Marina R.; Santiago, Michelle A.; Gonçalves, Natália T.; Schirmer, Brígida G. A.; Carneiro, Márcia M.; Reis, Fernando M.; Malamut, Carlos; Ferreira, Márcia C.
Endometriosis is a debilitating disease that still needs surgery to be confirmed. Endometriosis is associated with increased plasma levels of phosphatidylcholines. 18 F-fluorocholine ([ 18 F]FCH) is a radiopharmaceutical that is metabolized to phosphatidylcholine inside the cells and can be traced by positron emission tomography (PET). Here we evaluate [ 18 F]FCH as a potential tool for the noninvasive diagnosis of peritoneal endometriosis. Adult female Wistar rats had autologous uterine fragments dissected and grafted to the peritoneal wall to model peritoneal endometriosis. Ex vivo biodistribution assay and PET imaging studies were performed 30 minutes after [ 18 F]FCH administration. The [ 18 F]FCH uptake was 3-fold higher in endometriotic implant tissues than in muscle or peritoneum. Positron emission tomography imaging revealed the grafted uterine tissue in contrast to surrounding structures. Region-of-interest analysis of the reconstructed images showed higher accumulation of [ 18 F]FCH by endometriotic lesions, 0.34 (0.04)% of injected dose per gram of tissue (ID/g), in comparison with muscle tissue, 0.08 (0.01)% ID/g. However, sham implants with fat tissue were also detectable in PET imaging. These preliminary findings of [ 18 F]FCH uptake by ectopic uterine tissue implants and their localization by PET imaging encourage the future evaluation of this technique to detect small superficial endometriosis lesions in humans. Study protocols need to be further perfected and adapted for tests in women with endometriosis.